Computer Science and Architecture of Digitalization HRM - Rismawati Br Sitepu; Hartono Subagyo; Teofilus; Fahrul Riza; Iwang Suwangsih (Jurnal Penelitian Pendidikan IPA, 2025)
The advent of science and technology have revolutionized every facet of modern HR is no exception. Traditional HR with no digital science practices are being replaced by digital tools that offer more agility, precision, and scalability. Organizations today face dynamic market demands, requiring efficient talent management to stay competitive. The digitalization of Human Resources (HR) has redefined talent management by enhancing efficiency and effectiveness through advanced technologies like Artificial Intelligence, big data, and cloud computing. This study investigates how digital tools streamline HR operations, improve decision-making, and foster employee engagement. Key areas of focus include recruitment, performance management, employee engagement, and workforce analytics. The study also examines the challenges organizations face in adopting digital HR systems and proposes strategies to overcome them. Using a qualitative methods approach, data from industry reports, HR professionals, and employee surveys are analyzed to explore the impact of digitalization on key HR functions. Results indicate a significant improvement in recruitment efficiency, employee performance management, and workforce analytics. The discussion highlights the benefits, challenges, and strategies for successful implementation, concluding with recommendations for organizations aiming to maximize the potential of digital HR.